Pengaruh Talent Management dan Kompensasi Terhadap Employee Rentention pada Karyawan di Bank Muamalat KCU Yogyakarta - Miranda Novitalia; Dyah Diwanti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
This study aims to examine the effect of talent management and compensation on employee retention at Bank Muamalat KCU Yogyakarta. The population of this study consisted of all 100 employees, and a census sampling technique was applied. Data were collected through structured questionnaires and analyzed using a quantitative approach with Partial Least Square–Structural Equation Modeling (PLS-SEM) assisted by SmartPLS version 4.0. The results indicate that talent management does not have a significant effect on employee retention, suggesting that the existing talent management practices have not been perceived as a decisive factor in encouraging employees to remain with the organization. In contrast, compensation has a positive and significant effect on employee retention, with a path coefficient of 0.738, indicating that compensation is the most dominant factor influencing employees’ decisions to stay. Furthermore, the simultaneous testing shows that talent management and compensation explain 52.8% of the variance in employee retention, although the insignificant role of talent management weakens the overall combined effect.These findings imply that employee retention at Bank Muamalat KCU Yogyakarta is primarily driven by tangible and immediate rewards, particularly compensation, while talent management functions as a supporting factor with a long-term orientation. Therefore, improving compensation policies alongside strengthening the implementation of talent management is essential to achieve sustainable employee retention.